Implementasi aplikasi “Mentari” assessment berbasis kearifan lokal Sunda pada remaja untuk peningkatan literasi dan ketahanan mental - Hertini, Reni; Rohita, Tita; Wahyudin, Asep; Riyantina, Ade Sity; Cahyani, Gita; Berliani, Melin; Awaliyah, Rida Nurfarida; Mubarok, Resdyana (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Adolescent mental health is a critical issue currently of global, national, and local concern. According to data from the World Health Organization (WHO), more than 970 million people worldwide experience mental disorders, with depression and anxiety disorders being the two most common conditions. Specifically, the WHO states that approximately 1 in 7 adolescents aged 10–19 years experience a mental disorder. Purpose: To analyze the implementation of the